Developing a soft-scape standard for improving the landscape quality in Malaysia - Ibrahim, Roziya; Abd. Rahman, Nordin; Mohd Tahir, Osman (Faculty of Design & Architecture, Universiti Putra Malaysia, 2009)
The vision 'Towards a Garden Nation 2005' introduced by the Malaysian government in 1997 has boosted rapidly the landscape development throughout the country. The effort further continues with the vision towards 'The Most Beautiful garden Nation' by the year 2020 mooted in 2006. The landscape industry has than grown quite significantly to cater for demands in soft-scape materials and often works without proper control lead to devastating compromise in the landscape quality. Currently, this issue is critical as there is no specific quality standard to monitor and control the quality of soft-scape materials and works in Malaysia. Therefore, this paper intends to explore the need to develop a soft-scape standard to regulate the quality of soft-scape materials and works in Malaysia. The issues and problems relating to quality standard of soft-scape in landscape construction will be analysed through literatures review, documents analysis and interviews with the local professionals and experts in landscape development. These are further supported by researcher observations at the local landscape nurseries and the landscape construction site. Finally, recommendations are given on the development of the soft-scape standard for the local landscape industry players as reference in their landscape practices. A proper enforcement of this standard will help improve the landscape quality towards sustainability in Malaysia.